ملازمت پیشہ خواتین کو رفقاء خواتین سے درپیش تحدیات: اسلامی تعلیمات کی روشنی میں تدارک: Challenges Faced by Working Women from Female Colleagues: Prevention in the Light of Islamic Teachings - Ayesha Rehman; Dr. Amir Hayat (Al Manhal Research Journal, 2024)
In formal job market women represent 22 percent of labor force in Pakistan. The data of women participation in informal job sector is not available. Women face many economoic and socio-cultural challenges in the workplace. Discrimination in job opportunities, wages, harrassment and cultural barriers are often highlighted in the research. However, women face many challenges in the workplace from their colleages. From job opening to selection, and whether being subordinate or being an executive, there are many challenges which women face from fellow women on the work palce. These problems are rearly highlighted in the research studies. Present research study aims at pointing out the nature of challnages faced by working women from fellow colleages and providing solution to these challenges in the light of Islamic teachings. The study carried out in Sialkot, where panel discussion was arranged in a women college representing women from all job positions. The thematic analysis of data was carried out to draw results. The main challenges identified were then analysed in the light of Islamic teachings to propose a viable solution. The research concludes that challenges faced by worm from women arise due to divergence from Islamic teachings. All institutions of the society need to revert back to Islamic guidance to make working environment peaceful.